Noria and its derivatives as hosts for chemically and thermally robust Type II porous liquids. Issue 42 (18th October 2021) - Alexander, Francesca M.; Fonrouge, Sergio F.; Borioni, José L.; Del Pópolo, Mario G.; Horton, Peter N.; Coles, Simon J.; Hutchings, Benjamin P.; Crawford, Deborah E.; James, Stuart L.
Abstract : Porous Liquids (PLs) are a new class of material that possess both fluidity and permanent porosity. Here we identify Noria, a rigid cyclic oligomer as a new host for the synthesis of more robust Type II PLs. Abstract : Porous Liquids (PLs) are a new class of material that possess both fluidity and permanent porosity. As such they can act as enhanced, selective solvents and may ultimately find applications which are not possible for porous solids, such as continuous flow separation processes. Type II PLs consist of empty molecular hosts dissolved in size-excluded solvents and to date have mainly been based on hosts that have limited chemical and thermal stability. Here we identify Noria, a rigid cyclic oligomer as a new host for the synthesis of more robust Type II PLs. Although the structure of Noria is well-documented, we find that literature has overlooked the true composition of bulk Noria samples. We find that bulk samples typically consist of Noria ( ca. 40%), a Noria isomer, specifically a resorcinarene trimer, "R3" ( ca. 30%) and other unidentified oligomers ( ca. 30%). Noria has been characterised crystallographically as a diethyl ether solvate and its 1 H NMR spectrum fully assigned for the first time. The previously postulated but unreported R3 has also been characterised crystallographically as a dimethyl sulfoxide solvate, which confirms its alternative connectivity to Noria. Noria and R3 have low solubility which precludes their use in Type II PLs, however, the partially ethylated derivative Noria-OEt dissolves in the size-excluded solvent 15-crown-5 to give a new Type II PL. This PL exhibits enhanced uptake of methane (CH4 ) gas supporting the presence of empty pores in the liquid. Detailed molecular dynamics simulations support the existence of pores in the liquid and show that occupation of the pores by CH4 is favoured. Overall, this work revises the general accepted composition of bulk Noria samples and shows that Noria derivatives are appropriate for the synthesis of more robust Type II PLs.